The Reconstruction of Constructivist-Based Islamic Religious Education Learning in Enhancing Students' Understanding at SD NU 03 Bondowoso - Faisol Amin; Asyari Abdul Wafa; Tubi Heryandi (Journal of Contemporary Pedagogy and Learning Science, 2026)
Islamic Religious Education (IRE) plays a crucial role in developing students’ cognitive competencies while fostering religious, moral, and social character. However, IRE learning in elementary schools is frequently dominated by conventional instructional approaches that emphasize knowledge transmission and academic achievement, limiting students’ opportunities to develop meaningful understanding of Islamic teachings. This study aimed to analyze the reconstruction of constructivist-based Islamic Religious Education learning in enhancing students’ understanding at SD NU 03 Bondowoso and to identify the factors supporting and hindering its implementation. The study employed a qualitative case study design involving the principal, Islamic Religious Education teachers, and students as research participants. Data were collected through classroom observations, semi-structured interviews, and document analysis, and were analyzed using the interactive model of data reduction, data display, and conclusion drawing. The findings revealed that learning reconstruction was implemented through student-centered constructivist practices, the integration of Multiple Intelligences-based instructional strategies, the utilization of contextual learning environments, and the incorporation of religious programs such as Qiraati-based Qur’anic learning, Qur’an and hadith memorization, Arabic language instruction, and worship habituation activities. Supporting factors included school leadership, teacher competence, learning facilities, and parental involvement, while challenges involved variations in student characteristics and limitations in instructional innovation. The study demonstrates that constructivist-based learning reconstruction contributes to greater student engagement, motivation, and understanding of Islamic Religious Education.